(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Surgical management of Extradural Haematoma (EDH) in Closed Head Injury is an essential issue. Objective: The purpose of the present study was to compare the surgical outcome between early and delayed surgery of extradural haematoma (EDH) in closed head injury. Methodology: This comparative cross-sectional study was carried out from January 2010 to June 2011 for a period of one year and six months in the Department of Neurosurgery, Dhaka medical College Hospital, Dhaka, Bangladesh. All patients presented with traumatic head injury having extradural haematoma in any age with both sexes who were underwent surgical management were selected as study population. The patients were categorized into groups designated as group A or early surgery group where operation was done within 24 hours of head injury and group B or delayed surgery group where operation was done after 24 hours to 3 days of head injury. Inclusion of patients in group B was not intentional but due to delayed referral from primary and secondary hospitals of` different parts of’ the country. Glasgow coma scale (GCS) was used for initial assessment and Glasgow outcome scale (GOS) was applied to assess outcome in terms of neurological recovery in all patients. General and neurological examinations and findings were recorded. Surgical outcome was noted and recorded in the data collection sheet. Result: Eighty (80) patients of traumatic head injury with EDH operation (EDH operated within 24 hours and after 24 hours of head injury) were enrolled in this study. Mean (±SD) age of the patients of group A and group B was 32.66±16.65 and 33.23±13.38 respectively. In this study the patient’s age ranged from 3 years to 64 years. In group A, 6 patients were admitted with GCS (14-15) and 01 patient in group B. With GCS (9 13), 19 patients in group A and 22 patients in group B. With GCS (3-8), 15 patients were admitted in group A and 17 patients in group B. Out of all patients’ good recovery occurred in 80.0% in group A and 45.0% in group B. Moderate disability and severe disability in both group A and group B was 12.5% vs 30% and 7.5% vs 12.5% respectively. Furthermore 5.0% persistent vegetative state and 7.5% death occurred only among the patients of group B (p<0.05). Out of all patients good recovery occurred in 82.6% in group A and 54.0% in group B. Moderate disability and severe disability in both group A and group B was 10.0% vs 27.5% and 7.5% vs 13.51% respectively. 5.41% persistent vegetative state occurred only in patients of group B (p<0.05). Conclusion: In conclusion morbidity and mortality rate can be reduced in patients with EDH by early surgical intervention in better GCS score. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 24-28